# ITT: We go through the 3U paper and post up answers. (1 Viewer)

#### Scissors

##### Member
I'm stupid so I won't post up any answers.

Anyway, go!

Anybody?

#### scott.syd

##### New Member
i can try:
1(a) : -27
1(b): -3/(1-9x^2)^1/2
1(c): pi/3
1(d): 10264320
1(e): ((2)^1/2)/12
1(f): 3<x<5

2(a): 1/2
2(b): (11)^1/2
2(c): -5
2(d): 4.11

#### elliots

##### Member
scott.syd said:
i can try:
1(a) : -27
1(b): -3/(1-9x^2)^1/2
1(c): pi/3
1(d): 10264320
1(e): ((2)^1/2)/12
1(f): 3<x<5

2(a): 1/2
2(b): (11)^1/2
2(c): -5
2(d): 4.11

got all of those

#### poWerdrY

##### Member
someone post the proof for second last part of q7

#### Triple777ER

##### Vamos Rojas
post up the answers to the Question7 you fucking smart cunts

#### scott.syd

##### New Member
poWerdrY said:
someone post the proof for second last part of q7
LHS= y'(t1)/x'(t1)
=(Vsin-gt1)/Vcos
RHS=tan a - tan b
=h(t2-t1)/Vt1t2cos
sub t2= 2Vsin/g - t1
and t1t2= 2h/g

therefore: RHS= h (2Vsin/g -2t1)/V(2h/g)cos
=(Vsin-gt1)/Vcos
=LHS

#### independantz

##### Member
Anyone got the answers to the perms and combs? and 3a(ii)

#### poWerdrY

##### Member
scott.syd said:
LHS= y'(t1)/x'(t1)
=(Vsin-gt1)/Vcos
RHS=tan a - tan b
=h(t2-t1)/Vt1t2cos
sub t2= 2Vsin/g - t1
and t1t2= 2h/g

therefore: RHS= h (2Vsin/g -2t1)/V(2h/g)cos
=(Vsin-gt1)/Vcos
=LHS
OMFG!!!!! i didnt think of implicit differentiation!!!!!!! omfg!!!

#### poWerdrY

##### Member
independantz said:
Anyone got the answers to the perms and combs? and 3a(ii)
8!/2 ( as john behind barabara is half of all cases. easy i know, but i didnt think of it in the exam)

#### u-borat

##### Banned
scott.syd said:
LHS= y'(t1)/x'(t1)
=(Vsin-gt1)/Vcos
RHS=tan a - tan b
=h(t2-t1)/Vt1t2cos
sub t2= 2Vsin/g - t1
and t1t2= 2h/g

therefore: RHS= h (2Vsin/g -2t1)/V(2h/g)cos
=(Vsin-gt1)/Vcos
=LHS
wow nice solution.

i didn't quite get it, but i think the way you were meant to (cos implicit diff is only 4unit amirite?) was to get the general equation of the paraboal by getting rid of t in your general motion equations, then differentiate that, subbing in x=Hcotalpha then equate that to tan wierd squiggly thing.

didn't quite get the answer though

#### tacogym27101990

##### Member
poWerdrY said:
8!/2 ( as john behind barabara is half of all cases. easy i know, but i didnt think of it in the exam)
but i had a mind blank with the question and considered cases. took a long time
but same result =]

#### scott.syd

##### New Member
i'll put the other answers i got, not proofs though, they are too long:
3(a)(ii): -2=<x=<4/3
4(a)(ii): 12.44pm
4(b)(i): 7!= 5040 ways
5(a)(ii): y= 1-(1-2x)^1/2
5(a)(iii): 1/2
5(b): a=2/3 metres T=2pi/3 seconds
6(a)(ii): 96.0m
6(b): 0, 2pi/3, pi, 4pi/3, 2pi
6(c)(i): (p+q)!/(p!q!)
6(c)(ii): (p+q)!/p!q!

#### independantz

##### Member
Anyone got answers to 3a(ii) and the height of the tower for the 3d trig 6a(ii)

#### u-borat

##### Banned
i confirm everything.
nice job scottsyd.

#### independantz

##### Member
scott.syd said:
6(b): 0, 2pi/3, pi, 4pi/3, 2pi
i might be wrong but i got 0,pi/3,pi,5pi/3,2pi

#### u-borat

##### Banned
o shit, yeah i got what independantz got too.

#### conics2008

##### Active Member
srrhy guys I'm using itouch so it's hard but I'm confident with mine

#### poWerdrY

##### Member
u-borat said:
wow nice solution.

i didn't quite get it, but i think the way you were meant to (cos implicit diff is only 4unit amirite?) was to get the general equation of the paraboal by getting rid of t in your general motion equations, then differentiate that, subbing in x=Hcotalpha then equate that to tan wierd squiggly thing.

didn't quite get the answer though
thats what i thought, but then the equation of the parabola would be y= -ax(x-r). and i couldnt think of a way to get rid of a.

#### scott.syd

##### New Member
u-borat said:
wow nice solution.

i didn't quite get it, but i think the way you were meant to (cos implicit diff is only 4unit amirite?) was to get the general equation of the paraboal by getting rid of t in your general motion equations, then differentiate that, subbing in x=Hcotalpha then equate that to tan wierd squiggly thing.

didn't quite get the answer though
but i didn't do it by implicit diff, i just did normal differentiation coz the tan of the angle at the point was the vertical velocity/horizontal velocity. so ya. i wouldn't how else to do it.